Synthesis and Biological Evaluation of 4β-N-Acetylamino Substituted Podophyllotoxin Derivatives as Novel Anticancer Agents - Wei, Jinbao; Chen, Jinghong; Ju, Peijun; Ma, Le; Chen, Li; Ma, Weidong; Zheng, Tao; Yang, Guangyi; Wang, Yong-Xiang (Frontiers in Chemistry, 2019)
A series of novel podophyllotoxin derivatives obtained by 4β-N-acetylamino substitution at C-4 position were designed, synthesized, and evaluated for in vitro cytotoxicity against four human cancer cell lines (EC-9706, Hela, T-24 and H460) and a normal human epidermal cell line (HeCaT). The cytotoxicity test indicated that most of the derivatives displayed potent anticancer activities, especially, compound 12h showed high activity with IC50 values ranging from 1.21 to 22.78 μM, showing much better cytotoxic activity than the control drug etoposide (IC50: 8.43 to 78.16μM). Compound 12j exhibited promising cytotoxicity and selectivity against T24 and HeCaT cell lines with IC50 values of 2.68 and 49.08 μM, respectively. Compound 12g displayed potent cytotoxicity against Hela and T24 cells with low activity against HeCaT cell. According to the results of fluorescence-activated cell sorting (FACS) analysis, 12g induced cell cycle arrest in the G2/M phase accompanied by apoptosis in T24 and Hela cells. Furthermore, the docking studies were in agreement with the cytotoxicity data. These results showed that 12g was meriting further optimization and development as a new podophyllotoxin-derived lead compound.